2008
DOI: 10.1093/jpepsy/jsn016
|View full text |Cite
|
Sign up to set email alerts
|

Child versus Parent Report of Parental Influences on Children's Weight-related Attitudes and Behaviors

Abstract: Parent weight-related behaviors, both direct and indirect, are positively associated with child's weight-related attitudes and behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 22 publications
8
62
0
7
Order By: Relevance
“…It has been shown that parent and offspring reports show some disparity (Haines et al 2008;Keery et al 2006), possibly due to parental concerns about social desirability or over-reporting amongst criticism-sensitive adolescents (Baker et al 2000). However, as previously stated, studies have consistently reported offspring-reports of parental behaviors to be more strongly associated with body shape and eating outcomes than parent-reports (Haines et al 2008;Kanakis and Thelen 1995;Keel et al 1997;Keery et al 2006). Adopting the point of view of the adolescent limits the scope of the results in terms of conclusions to be drawn regarding parental behavior, but in exchange focuses on the variables that demonstrate the strongest relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that parent and offspring reports show some disparity (Haines et al 2008;Keery et al 2006), possibly due to parental concerns about social desirability or over-reporting amongst criticism-sensitive adolescents (Baker et al 2000). However, as previously stated, studies have consistently reported offspring-reports of parental behaviors to be more strongly associated with body shape and eating outcomes than parent-reports (Haines et al 2008;Kanakis and Thelen 1995;Keel et al 1997;Keery et al 2006). Adopting the point of view of the adolescent limits the scope of the results in terms of conclusions to be drawn regarding parental behavior, but in exchange focuses on the variables that demonstrate the strongest relationships.…”
Section: Discussionmentioning
confidence: 99%
“…In this type of study, offspring-reported data has been reported by a number of studies to be more strongly associated with body shape and eating outcomes than parent-reports (Haines et al 2008;Kanakis and Thelen 1995;Keel et al 1997;Keery et al 2006). All our measures therefore assessed adolescent self-reported perceptions of their parents' attitudes, behaviors and messages.…”
Section: Measurementioning
confidence: 99%
“…Because parents' own dieting behavior has been shown to be associated with adolescents' body satisfaction and dieting behaviors in these and other data [27,28], dieting behavior of the same-sex parent (at Time 1) was included in the present analysis to adjust for this additional social influence. The construct was assessed with one item (''My mother/father.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have investigated the concurrence of parents and children on reporting children's outcomes, and most of these studies show that children are reliable reporters (e.g., Herjanic, Herjanic, Brown, & Wheatt, 1975;Herjanic & Reich, 1997). Additionally, a recent study found that children's reports of indirect parental behavior are more consistently associated with children's adjustment than parent reports (Haines, Neumark-Sztainer, Hannan, & Robinson-O'Brien, 2008). Furthermore, all research questions were investigated separately for boys and for girls, because several studies have shown gender differences in how children deal with divorce and remarriage (e.g.…”
Section: Research Aimsmentioning
confidence: 99%